2021
DOI: 10.1021/acs.jced.0c00618
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mixed MEA-Based Solvents Featuring Ionic Liquids and NMP for CO2 Capture: Experimental Measurement of CO2 Solubility and Thermophysical Properties

Abstract: Alkanolamine solutions are used in the industry worldwide to remove carbon dioxide and hydrogen sulfide from natural gas, but such technologies have disadvantages. This study aimed to investigate the new hybrid amine solvents for carbon dioxide capture and their potential to reduce the disadvantages of amine technology. The solubility of carbon dioxide in hybrid solvents with different mixtures of monoethanolamine, water, n-methyl-2-pyrrolidone, 1-butyl-3-methylimidazolium trifluoromethanesulfonate, and 1-buty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Literature data for the solubility of CO 2 (moles of CO 2 in liquid phase divided by the total moles of solvent) in NMP (▲); and MEA (1) + NMP (2) with different MEA mass compositions: w 1 = 0.1025 (●), w 1 = 0.2032 (■), and w 1 = 0.3037 (◆) at 313.15 K …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature data for the solubility of CO 2 (moles of CO 2 in liquid phase divided by the total moles of solvent) in NMP (▲); and MEA (1) + NMP (2) with different MEA mass compositions: w 1 = 0.1025 (●), w 1 = 0.2032 (■), and w 1 = 0.3037 (◆) at 313.15 K …”
Section: Resultsmentioning
confidence: 99%
“…32 Results indicated that replacing water with NMP in the aqueous MEA solvent with MEA mass fraction of 0.1 greatly increases CO 2 solubility by almost 81% at pressures between 0.21 to 2 MPa. 32 Despite this, it is important to conduct further research on the solubility of other natural gas constituents, such as methane and ethane, in hybrid solvents. This information is crucial for process design and optimization, as well as for comparing the loss of hydrocarbons between conventional and hybrid solvents.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In nonaqueous media, speciation among carbamic acid and carbamate is similarly sensitive to temperature and pressure as in aqueous media, with higher temperatures and lower partial pressures of CO 2 favoring carbamate ( Kortunov et al., 2015b ). Solvents examined for nonaqueous capture range broadly, for example, dimethyl sulfoxide ( Kortunov et al., 2015b ), ethanol ( Versteeg and van Swaaij, 1988 ), propylene carbonate ( Karlsson et al., 2019 ), or n-methyl pyrrolidone ( Ebrahiminejadhasanabadi et al., 2021 ). These solvents are not always relevant to electrochemical systems as discussed later.…”
Section: Parameters Governing the Capture Process And Resulting Solut...mentioning
confidence: 99%
“…Therefore, methods to control, capture, and use industrial CO 2 emissions should be widely studied. For example, Ebrahiminejadhasanabadi et al 6 . have studied CO 2 capture using a mixture of ionic liquids and N‐methylpyrrolidone (NMP) as a solvent and Zhang et al 7 .…”
Section: Introductionmentioning
confidence: 99%